2019
DOI: 10.1142/s179354581950010x
|View full text |Cite
|
Sign up to set email alerts
|

Combined spatial frequency spectroscopy analysis with visible resonance Raman for optical biopsy of human brain metastases of lung cancers

Abstract: The purpose of this study is to examine optical spatial frequency spectroscopy analysis (SFSA) combined with visible resonance Raman (VRR) spectroscopic method, for the first time, to discriminate human brain metastases of lung cancers adenocarcinoma (ADC) and squamous cell carcinoma (SCC) from normal tissues. A total of 31 label-free micrographic images of three types of brain tissues were obtained using a confocal micro-Raman spectroscopic system. VRR spectra of the corresponding samples were synchronously c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…We observed that Raman peaks due to carotenoids, proteins, and lipids from the margin tissues were different from those in the tumor tissues. Similar Raman spectral changes were also observed in skin, breast, and heart tissue in our previous studies [ 26 , 34 , 40 , 41 , 45 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We observed that Raman peaks due to carotenoids, proteins, and lipids from the margin tissues were different from those in the tumor tissues. Similar Raman spectral changes were also observed in skin, breast, and heart tissue in our previous studies [ 26 , 34 , 40 , 41 , 45 , 46 , 47 ].…”
Section: Discussionsupporting
confidence: 88%
“…Raman spectral changes can reveal the metabolic processes of brain tissue [ 24 , 25 , 30 ] and can potentially be used for margin assessment, even during surgery [ 24 , 30 , 31 , 32 , 33 , 34 , 35 ]. Raman spectroscopy techniques have been used to study human bladder cancer, esophageal cancer, gastrointestinal cancer, cervical cancer, skin melanoma lesions, lung cancer, breast cancer, and brain tumors, not only ex vivo but also in vivo [ 15 , 16 , 19 , 20 , 21 , 22 , 22 , 23 , 26 , 27 , 28 , 31 , 33 , 36 , 37 , 38 , 39 , 40 ]. Besides solid tumors, Raman spectroscopy has also been used to detect vulnerable atherosclerotic plaques, atherosclerotic abdominal aortic tissues, and nerve tissues, and even the cerebrospinal fluid and serum of patients [ 41 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, conventional fluorescent molecules cannot meet these criteria. In contrast, surface‐enhanced Raman scattering (SERS) nanotags can produce strong and unique fingerprint Raman signals under laser excitation, [ 10–13 ] leading to distinct spectral features from the background of regular ink. Compared with fluorophores that are commonly applied in security ink, [ 5,6,14,15 ] SERS nanotags show a much better stability as well as a greater multiplexing capability due to the narrower spectral linewidth, [ 16 ] allowing multiplexed steganography.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the super-resolution optical microscopes have achieved incredible success in revealing nanoarchitectures in single cells. However, the human-made semiconductor nanostructures in IC chips have hardly been imaged or characterized by super-resolution optical microscopes because of their inapplicability for fluorescence labeling. Label-free and far-field optical super-resolution nanoscopy was thought to provide tremendous opportunities for direct and easy IC visualization and inspection, and it has also been theoretically and experimentally pursued by various methods in Raman, , coherent anti-Stokes Raman scattering (CARS), stimulated Raman scattering (SRS), and pump–probe (PP) microscopes. Pump–probe microscopes have demonstrated super-resolution imaging of graphene by applying excessive laser power or higher photon energy in the donut beam to saturate the signal therein. , Although the pump–probe signal was also observed in copper, the saturation is not applicable to copper wires in ICs.…”
Section: Introductionmentioning
confidence: 99%